Equilíbrio eletrolítico e condicionamento térmico precoce na criação de frangos de corte submetidos ao estresse térmico /Mayara Maia Rodrigues. -: Mayara Maia Rodrigues. - - Rodrigues, Mayara Maia [UNESP] (2015)
In tropical climates, the heat is the major factor limiting the production of broiler chickens, and is responsible for inducing a high mortality, especially in the finishing phase. The electrolyte balance (EB) and early thermal conditioning (ETC) are two techniques to alleviate the negative effects of heat stress. Thus, this study aimed to evaluate the possible interactions and the effects of dietary electrolyte balance and application of early thermal conditioning of the feed intake (kg), body weight (kg), feed conversion (kg), mortality (%), energy bio-economic conversion index (Mcal/kg), moisture faeces (%), carcass weight (kg), body cavity fat (g) and breast color (L*a *b*) in cuts of chicken chronic heat stress conditions. Thus, the electrolyte balance (EB = K+Na-Cl) was set to 300 mEq / kg and electrolyte ratio (ER = [(K+Cl)/Na]) 3: 1 by non-linear PPFR program. They were housed 640 male chicks a day old, distributed in a factorial arrangement 2x2 (with and without ETC and with and without EB) in a completely randomizeddesign in 32 boxes (8 replicates per treatment). The thermal conditioning was applied on the fifth day old birds for 24 hours at 36 °C and only half of the batch (320 birds). After this period, all the birds were transferred to boxes (20 birds/box), with the bed waste acerola. Chronic heat stress (6 hours at 32 °C) was applied to all the birds of 35 after 39 days of age, being electronically monitored temperature and humidity of the warehouse, in relation to the microclimate of the area / height of the birds. The results indicated that: a) there was no interaction between the two techniques, EB and ETC; b) diets with EB resulted in more expensive ration besides increasing the moisture of faeces, but there was lower mortality; c) ETC resulted in a pale staining in breast samples. Thus, it can be concluded that both the EB and ETC are not effective for minimizing the negative effects of chronic heat stress in broilers